2016
DOI: 10.1111/dmcn.13173
|View full text |Cite
|
Sign up to set email alerts
|

Observational pilot study of reported symptoms of obstructive sleep apnoea in children with epilepsy

Abstract: This study suggests higher rates of symptoms of OSA and EDS in CWE compared with typically developing children. AEDs may be a confounding factor, but do not alone account for the associations seen. Further studies including polysomnography to verify the presence (rather than suggestion by questionnaire) of OSA are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
0
14
1
Order By: Relevance
“…In Ethiopia, 19% of college students were found to have high risk for clinical OSA (11). A study in Egypt found a prevalence of 42% among children with epilepsy, with an observation that OSA contributed to seizure frequency (6). Nigerian adult hypertensives were found to have a 52% prevalence of clinical sleep apnea while patients with type II diabetes mellitus had a 27% prevalence in the same population (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…In Ethiopia, 19% of college students were found to have high risk for clinical OSA (11). A study in Egypt found a prevalence of 42% among children with epilepsy, with an observation that OSA contributed to seizure frequency (6). Nigerian adult hypertensives were found to have a 52% prevalence of clinical sleep apnea while patients with type II diabetes mellitus had a 27% prevalence in the same population (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of OSA is significantly higher in the epilepsy group-35% versus healthy children-7.4%. In refractory epilepsy, 44% children have the diagnosis of OSA, in other form of epilepsy around 31% [32,33]. It is especially important for clinicians, who frequently under-recognize and misinterpret sleep disorders in epilepsy patients.…”
Section: Sleep and Epilepsymentioning
confidence: 99%
“…Major risk factors for sleep apneas in childhood epilepsy include poor seizure control and on multiple antiepileptic medications [18]. Urquhart et al [19] studied obstructive sleep apnea symptoms among 33 children with epilepsy (21 males, 12 females), along with 42 controls (20 males, 22 females). They found that 55% children with epilepsy scored 0.33 or higher on the sleep-related breathing disorder questionnaire compared with 7% in the comparison group (p<0.001).…”
Section: Obstructive Sleep Apnea (Osa)mentioning
confidence: 99%